Genome-Wide Association Study of Human Immunodeficiency Virus (HIV)-1 Coreceptor Usage in Treatment-Naive Patients from An AIDS Clinical Trials Group Study. (22nd May 2014) - Henrich, Timothy J.; McLaren, Paul J.; Rao, Suhas S. P.; Lin, Nina H.; Hanhauser, Emily; Giguel, Francoise; Gulick, Roy M.; Ribaudo, Heather; de Bakker, Paul I. W.; Kuritzkes, Daniel R.
Abstract : Phenotypic determination of HIV-1 coreceptor usage was performed on 593 pre-treatment plasma HIV-1 samples from treatment-naive participants in ACTG A5095. No human genetic variants were significantly associated with virus able to use CXCR4 for entry at the genome-wide level. Abstract: Objectives.  We conducted a genome-wide association study to explore whether common host genetic variants (>5% frequency) were associated with presence of virus able to use CXCR4 for entry. Methods.  Phenotypic determination of human immunodeficiency virus (HIV)-1 coreceptor usage was performed on pretreatment plasma HIV-1 samples from treatment-naive participants in AIDS Clinical Trials Group A5095, a study of initial antiretroviral regimens. Associations between genome-wide single-nucleotide polymorphisms (SNPs), CCR5 Δ32 genotype, and human leukocyte antigen (HLA) class I alleles and viral coreceptor usage were explored. Results.  Viral phenotypes were obtained from 593 patients with available genome-wide SNP data. Forty-four percent of subjects had virus capable of using CXCR4 for entry as determined by phenotyping. Overall, no associations, including those between polymorphisms in genes encoding viral coreceptors and their promoter regions or in HLA genes previously associated with HIV-1 disease progression, passed the statistical threshold for genome-wide significance ( P < 5.0 × 10 −8 ) in any comparison. However, the presence of viruses able to use CXCR4 for entry was marginally associated with the CCR5 Δ32 genotype in the nongenome-wide analysis. Conclusions.  No human genetic variants were significantly associated with virus able to use CXCR4 for entry at the genome-wide level. Although the sample size had limited power to definitively exclude genetic associations, these results suggest that host genetic factors, including those that influence coreceptor expression or the immune pressures leading to viral envelope diversity, are either rare or have only modest effects in determining HIV-1 coreceptor usage.